COMPLETE HEALING OF A LARGE PERIAPICAL LESION FOLLOWING CONSERVATIVE ROOT CANAL TREATMENT IN ASSOCIATION WITH PHOTODYNAMIC THERAPY: A CASE REPORT WITH 5TH-YEAR FOLLOW-UP - Cristian Giuroiu; Tudor Hamburda; Anca Melian; Claudiu Topoliceanu; Sorin Andrian; Mihaela Salceanu (Romanian Journal of Oral Rehabilitation, 2020)
The aim of this case report was to assess the effectiveness of antimicrobial photodynamic therapy when associated with non-surgical endodontic treatment of large periapical cyst. Case report: A 52-years-old female patient complained of sharp pain in the upper maxillary anterior area of the mouth. The clinical exam showed for tooth 1.2. moderate dental dyschromia, slightly positive axial percussion and loss of hard bone substance of about 0,5 cm2. As well as negative response to thermal tests. The non-surgical endodontic treatment was associated to photodynamic therapy performed by diode laser 808nm following the irrigation with. Theroot canals were filled with Ca(OH)2 paste for 14 days. The paste was changed after 14 days, and the root canal photodynamic therapy was repeated. In the third session it was performed the definitive root canal filling and coronal-radicular reconstruction. Results: check-ups performed at 6 months, 12 months, 2 years and 5 years, demonstrated progressive healing of treated large periapical cyst, with total absence of signs or symptoms. Conclusion: the addition of photodynamic therapy to conventional endodontic treatment can increase the reduction of microbial load in the endodontic space and the long-term success rate in non-surgical treatment of large periapical cysts